Morpho-Semantic Study of the Microtoponyms of Ouadhia (Tizi Ouzou): Structure, Classification and Interpretation: Étude morpho-sémantique des microtoponymes de Ouadhia (Tizi-Ouzou): structure, classification et interprétation - Terbouche , Fazia; Djemai , Salem (Maalim, 2026)
This article provides a morpho-semantic analysis of microtoponyms in the Ouadhia region (Tizi-Ouzou) based on a corpus collected through fieldwork. The central research question aims to determine how the linguistic structure of microtoponyms reflects the geographical, social, and cultural characteristics of the local space. The study employs a descriptive and interpretative approach based on the identification of generic and specific elements, as well as a thematic classification. The corpus consists of microtoponyms gathered from native speakers and validated by cartographic sources. The results demonstrate that these designations reflect a close interaction between humans and their environment, integrating data related to topography, hydrology, human activities, and social organization. Thus, microtoponyms emerge as linguistic and cultural markers of territorial anchoring.